Identification and biocellulose production of Gluconacetobacter strains isolated from tropical fruits in Thailand - Daungjai Ochaikul (Maejo International Journal of Science and Technology, 2013)
Two hundred and four strains of biocellulose (BC)-producing Gluconacetobacter strains were isolated from 48 rotten tropical fruits collected in Thailand. Twenty-nine representative isolates were selected from each of the 16 isolation sources and identified by morphological, physiological and biochemical characteristics and 16S rRNA gene sequence analysis. The selected 29 isolates were divided into seven subgroups within the Gluconacetobacter xylinus group of the genus Gluconacetobacter and identified as Gluconacetobacter oboediens (subgroup I, five isolates), Gluconacetobacter rhaeticus (subgroup II, one isolate), Gluconacetobacter hansenii (subgroup III, seven isolates), Gluconacetobacter swingsii (subgroup IV, two isolates) and Gluconacetobacter sucrofermentans (subgroup V, two isolates). The remaining isolates were grouped into subgroups VIa (three isolates) and VIb (nine isolates). All the isolates were cultured in Hestrin-Schramm (HS) medium statically at 30C for 7 days to determine cellulose production capability. Of the 29 isolates, isolate PAP1 (subgroup VIb, unidentified) gave the highest yield (1.15 g/L) of BC. However, the BC yield increased threefold (3.5 g/L) when D-glucose in HS medium was replaced by D-mannitol.